Study Investigation The Risk Factors of Toddlers with Low Nutritional Status in The North Coast of Java, Indonesia - widya addiarto; Yulia Rachmawati Hasanah (Jurnal Kesehatan dr. Soebandi, 2023)
Today, one of the problems in the world that is never finished was low nutritional status. Toddlers nutritional are the measure of the success nutritional status. The development of toddlers can be seen from their nutritional status, whether nutritional intake is in accordance with needs or not. Every toddler has a different nutritional status depending on the nutritional intake received every day. Nutrition monitoring in toddlers can be done regularly through Posyandu or pediatricians. The risk of low nutritional status in children is caused by several factors, including internal factors and other external factors. According to UNICEF in 2020 estimates that 45.4 million of toddlers are acutely malnutrition. In 2021 the incidence of low nutrition status with stunting in Indonesia is 24.4%, East Java Province is 23.5% and Probolinggo Regency is 23.3%. This study used a descriptive analytic method with a cross sectional approach. The sample used in this study was 63 mothers who had toddlers. This study uses a questionnaire distributed to all respondents via google form then the data is processed to determine the dominant factors that influence the incidence of stunting in toddler. The results of a multivariate test of all the variables that most dominantly affect stunting, the strength of the relationship from the largest to the smallest. are: body weight (OR=83,664), diet (OR=15728), height (OR=8,977) and breast feeding (OR=0,832). Exclusive breastfeeding is highly recommended because it is very beneficial for the child's growth and development. Breast milk contains various substances that are beneficial for the body. Therefore, it is important for mothers to give breast milk to newborns to prevent babies from various diseases and for good brain growth . Keyword: Stunting, Nutritional Status, Toddler, Risk Factors